NAEP Conference 2020: ‘Whose placement is it anyway?’ - National Association of Educators in Practice , NAEP (International Journal of Practice-based Learning in Health and Social Care, 2021)
The United Kingdom’s National Association of Educators in Practice (NAEP) has published the peer-reviewed abstracts that had been accepted for the 2020 Conference, cancelled because of the COVID-19 pandemic. The collected abstracts can be downloaded from <a href="https://eur01.safelinks.protection.outlook.com/?url=https%3A%2F%2Fnaep-uk.org%2Fwp-content%2Fuploads%2F2021%2F04%2FPublication-of-peer-reviewed-abstracts-2020-conference-final-12.04.21.doc.pdf&data=04%7C01%7Ccsx071%40coventry.ac.uk%7C314105b4944840acdc7208d90afd1fca%7C4b18ab9a37654abeac7c0e0d398afd4f%7C0%7C0%7C637552904533009310%7CUnknown%7CTWFpbGZsb3d8eyJWIjoiMC4wLjAwMDAiLCJQIjoiV2luMzIiLCJBTiI6Ik1haWwiLCJXVCI6Mn0%3D%7C1000&sdata=tznAKCSzsV251JKlPt%2BZkgyl7KX7dtazmb93zjgZNm8%3D&reserved=0">https://naep-uk.org/wp-content/uploads/2021/04/Publication-of-peer-reviewed-abstracts-2020-conference-final-12.04.21.doc.pdf